An Epidemiological and Multidrug Resistance Study for E. coli Isolated from Urinary Tract Infection (Three Years of Study) - Mahde S. Assafi; Fawwaz F. Ali; Reem Fouad Polis; Nisreen Jawad Sabaly; Sozan Muhsin Qarani (مجلة بغداد للعلوم)
Uropathogenic E. coli (UPEC) is problematic and still the leading cause of urinary tract infections worldwide. It is developed resistance against most antibiotics. The investigation, surveillance system, and efficient strategy will facilitate selecting an appropriate treatment that could control the bacterial distribution. The present study aims to investigate the epidemiology and associated risk factors of uropathogenic E. coli and to study their antibiotic resistance patterns. 1585 midstream urine specimens were collected from symptomatic urinary tract infections (UTI) patients (225 males and 1360 females) admitted to Zakho emergency hospital, Zakho, Kurdistan Region, Iraq from January 2016 until the end of December 2018. Specimens were inoculated on blood and MacConkey plates and incubated at 37оC for 24 hours. Uropathogenic E. coli was diagnosed based on gram staining, colony characteristics, and standard biochemical tests in accordance with local standards and guidelines. All isolates were screened for their antibiogram pattern using the disk diffusion method based on the Clinical and Laboratory Standards Institute guidelines. The results showed that out of 1585 urine specimens, 1026 (64.7%) were UTIs positive with a statistically higher rate in 2016 (83.6%) (P< 0.0001). The UTIs frequency in females was significantly higher than males (P< 0.0001). Generally, the uropathogenic E. coli represented 21.1% with the highest level in 2016 (22.9%). The uropathogenic E. coli rate was higher, statistically not significant, in females (21.4%) than males (18.5%) (P=0.4946). Additionally, through the three years of study, uropathogenic E. coli (UPEC) was in high frequency in February and May 2016. The female’s age group from 20 to 39 years was the most vulnerable (46%) form total infected females, while those from 70-74 years (1%) were the least susceptible in males and females. A high percentage (80.56 %) of multidrug resistance E. coli isolates was observed with high resistance against -lactamase and macrolides antibiotics. However, higher sensitivity was towards imipenem and meropenem. In conclusion, the wrong and overuse of antibiotics will increase the resistance rate of E. coli. For this reason, proper use of available antibiotics is necessary. Also, the educational programs and periodic monitoring of antimicrobial susceptibility are essential for reducing the antibiotic resistance rate.